Kingdom of the Netherlands : Aruba. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights Aruba's recession, which began around mid-2015. Real GDP contracted by 0.5 and 0.2 percent in 2015 and 2016, respectively. Weakness in activity was broad based in 2016. Domestic demand contracted by 3.0 percent. Exports grew only 0.3 percent owing to weak tourism and shrinking nontourism exports. Imports contracted by 3.5 percent, reflecting weak demand on the back of fiscal consolidation and weak tourism growth. Monetary policy was unchanged during 2015-16. The banking system remains resilient. Banks maintain elevated capital buffers, have relatively low nonperforming loans, and are profitable.